Sustainable and inclusive community heritage tourism in the Makgabeng- Blouberg Region, Limpopo Province, South Africa - Radebe, Nondumiso Bongekile (My University, 2017)
Attaining socio- economic development is a priority that ranks high on the development plans of Governments in different parts of the world. In order to achieve this, the use of community based heritage resources as features in heritage tourism destinations has become common practice. Yet, the concept of development can be intimidating, particularly to communities in rural settings. Therefore, the introduction of development through the use of heritage resources that they are familiar with makes the process much more relatable. However, challenges come about when communities are unable to receive the anticipated benefits due to a lack of sustainability of some of these community based projects. Rich in cultural heritage resources, the MBCBHTP Located in the BLM of the CDM in the Limpopo Province is a project that seeks to bring about community development through the use of the regions heritage resources. It seeks to initiate a heritage tourism market and contribute to the conservation of the heritage resources that are under threat. The project also combats a number of social ills including unemployment, poverty and illiteracy amongst the communities of the MB region. Since its initiation in 2012, the project is well into its implementation phase. In an effort to combat some of the factors that lead to non-beneficial projects, a long term plan for the sustainability for the project is needed. Following a review of the project plans and objectives, engagement with project stakeholders and the local MB community; this study seeks to develop a unique sustainability model for the MBCBHTP. The model provides active strategies for working towards sustainability through an inclusive and collaborative effort that ensures that communities involved in the MBCBHTP receive continued benefits long after the project timeline lapses.
A thesis submitted in the fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, South Africa , November 2017.
Keywords: Heritage tourism--South Africa; Tourism--South Africa; Community development--South Africa